The Adolescent’s sexual behavior and its correlates: A Systematic Review - Hastuti, Puji; Yunitasari, Esti; Triharini, Mira; Saidah, Qoriila (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Abstract Adolescents aged 13-15 years are a group vulnerable to risky sexual behavior. Many studies have been conducted to find the factors that influence it. This paper aims to analyze scientific evidence of factors that influence adolescent sexual behavior from various research results. The study design was a literature review on the adolescent population. Researchers conducted a literature search from empirical studies spanning the years 2017-2022 identified through the Scopus, Ebscohost, Science direct, Sage, Proquest, Springer Link and Google Scholar databases. The initial search found 8399 articles, which were narrowed down to 14 articles through inclusion criteria and exclusion criteria. The study includes research with various quantitative and qualitative designs taken from several countries. The data were analyzed using a qualitative synthesis approach. The results of the analysis show that there are many factors related to risky sexual behavior in adolescents. These factors are grouped into 4 major groups. Interpersonal factors (the role of peers), social environmental factors (economic activities, tourist interests, social norms,), individual factors (biological responses, ignorance, knowledge, lack of information, religious understanding, attitudes, self-esteem, motivation, use of social media), family factors (social economy, closeness of parents, communication between parents and children). Keywords: Systematic review, sexual behavior, adolescents